2010
DOI: 10.1007/s00449-010-0429-3
|View full text |Cite
|
Sign up to set email alerts
|

Improved expression of recombinant cytochrome P450 monooxygenase in Escherichia coli for asymmetric oxidation of sulfides

Abstract: Escherichia coli BL21 as production strain for the production of cytochrome P450 monooxygenase (P450SMO) from Rhodococcus sp. in high yields was developed. The expression was first optimized with a series of flask experiments testing several key parameters for their influence on the expression level and enzyme activity. The optimal process parameters found in the flask experiments were verified in a cultivation process in a 5-L bioreactor. Glycerol proved to be superior over glucose as carbon source. Low disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Zhang and co-workers reported that dO 2 concentrations below 10% were conducive to active P450 expression and Vail and co-workers reported that high dO 2 concentrations led to an increase in misfolded protein compared with lower concentrations, and even used a concentration <1% for cultivation. Lu and co-workers found, however, that it was important not to limit dissolved oxygen levels [ 39 , 46 , 51 ].…”
Section: Strategies For P450 Production In Microbialsmentioning
confidence: 99%
“…Zhang and co-workers reported that dO 2 concentrations below 10% were conducive to active P450 expression and Vail and co-workers reported that high dO 2 concentrations led to an increase in misfolded protein compared with lower concentrations, and even used a concentration <1% for cultivation. Lu and co-workers found, however, that it was important not to limit dissolved oxygen levels [ 39 , 46 , 51 ].…”
Section: Strategies For P450 Production In Microbialsmentioning
confidence: 99%
“…Heterologous production of the P450 enzyme (P450SMO) from Rhodococcus sp. ECU0066 in E. coli cells was also reported to be higher under low induction temperatures (20°C and 25°C) than under high induction temperatures (30°C and 37°C) [18]. Moreover, CYP53A15 would be unstable and rapidly inactivated under mesophilic conditions higher than 25°C, which is also the case for other P450 enzymes, including…”
Section: Resultsmentioning
confidence: 94%
“…The authors suggested that the oxygen transfer rates could be controlled by manipulation of the inlet air pressure, which resulted in increased cyt b5 productivity. As shown by other studies, the amount of available oxygen must be balanced between cell growth and protein yields, since higher oxygen concentration may favor cell growth, but increase oxidative stress within the cells, whilst anoxic conditions may limit amino acid production and plasmid stability [ 45 , 46 , 47 ]. In the present study, the geometry and k L a values reached in the two types of lab-scale bioreactors used, the aeration rate, the stirring speeds, and the PID parameters to control the dissolved oxygen concentration influenced both the cell density and the yield of cyt b5 reached ( Figure 2 , Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%